Gene Editing to Accelerate Crop Breeding - Dhugga, Kanwarpal S. (Frontiers in Plant Science, 2022)
Recent advances in biotechnology have helped increase the frequency and specificity of gene editing to an extent that introducing gene variants directly in elite varieties has become possible. In comparison to the conventional approach of crossing an elite recipient line with an exotic donor parent to introduce the trait of interest followed by repeated backcrossing, direct introduction of major-effect gene variants into elite varieties saves time and resources, and eliminates yield drag resulting from the residual donor genes at the end of backcrossing.